PhET Simulation Instruction and its Effects on Students’ Motivation to Learn Physics (London Journal of Research In Humanities and Social Sciences, 2023)
The study investigated the effect of Physics Education Technology (PhET) simulated instruction on students’ motivation to learn electricity concepts in physics. Questionnaire for Students’ Motivation Towards Science Learning (SMTSL) was used to assess Senior High School students’ motivation to learn electricity concepts after they were taught in a demonstrative classroom and an exploratory classroom using the Physics Education Technology (PhET) simulation instruction. Sequential explanatory mixed methods design was used. The sample consisted of sixty-three (63) first-year Senior High School Science students. Posttest scores revealed that students’ motivation to learn electricity concepts significantly increased after they were taught electricity concepts with the PhET interactive simulation in both demonstrative classroom (M = 3.26; SD = 0.29) and exploratory classroom (M = 3.38; SD = 0.15).It was also found that the mean scores of students on all the motivation scales such as: self-efficacy, physics learning value, learning environment stimulation andactive learning strategy, increased significantly except performance goal which recorded a lower mean after using the PhET simulation to teach. It is recommended that teachers should use the PhET simulation as an instructional resource for teaching electricity concepts since it has the potential to increase students’ motivation to learn physics.
Keywords: demonstrative instruction; electricity concepts; exploratory instruction; interactive instruction; motivation; PhET simulated instruction